2021
DOI: 10.3390/ijerph18094460
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Hyperbaric Oxygen Therapy and Corticosteroid Therapy in Acute Acoustic Trauma: 15 Years’ Experience at the Czech Military Health Service

Abstract: Background: Acute acoustic trauma (AAT) ranks, among others, as one common cause of inner ear function impairment, especially in terms of military personnel, who are at an increased exposure to impulse noises from firearms. Aim of this study: 1. We wanted to demonstrate whether early treatment of AAT means a higher chance for the patient to improve hearing after trauma. 2. We find the answer to the question of whether hyperbaric oxygen therapy (HBO2) has a positive effect in the treatment of AAT. Methods: We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The importance of early steroid treatment after AAT injury (within 24 h) is supported by Holy et al [2021], showing a direct correlation between the onset of treatment and audiometric outcomes; the best outcomes were observed in patients who were treated within 24 h after AAT injury. Patients who were treated within 7 days showed better outcomes compared to those who started treatment later than 7 days after AAT injury [Holy et al, 2021]. In addition, the authors offered a "rescue" protocol including HBOT in patients who showed no audiometrical improvement after 7 days of oral steroid treatment.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The importance of early steroid treatment after AAT injury (within 24 h) is supported by Holy et al [2021], showing a direct correlation between the onset of treatment and audiometric outcomes; the best outcomes were observed in patients who were treated within 24 h after AAT injury. Patients who were treated within 7 days showed better outcomes compared to those who started treatment later than 7 days after AAT injury [Holy et al, 2021]. In addition, the authors offered a "rescue" protocol including HBOT in patients who showed no audiometrical improvement after 7 days of oral steroid treatment.…”
Section: Discussionmentioning
confidence: 93%
“…We acknowledge some limitations: (1) our study is limited by its retrospective nature; however, randomized control trials on the subject are not ethically feasible (2) because all our study subjects were recruits of young age (18-35 years), without any substantial morbidities and contraindications to steroid therapy, and thus our findings may not be generalizable to subjects with comorbidities presenting with AAT injury; (3) HBOT, with or without concurrent steroid treatment, is increasingly being investigated as playing a major role in AAT injury treatment [Yilikoski et al, 2008;Oya et al, 2019;Holy et al, 2021]. In our study cohort, it was not part of our study protocol, and therefore we cannot comment on the efficacy of this modality; (4) we observed a tendency to prescribe oral steroid treatment to subjects presenting with more severe hearing losses, when compared to those presenting with milder losses, as documented in the first audiometry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation